Religiosity-Based on Nurse Performance Model in Ibnu Sina Hospital - Ahri, Reza Aril; Rusydi, Arni Rizqiani; Haeruddin, Haeruddin; Yusuf, Rezky Aulia (Window of Health : Jurnal Kesehatan, 2024)
Nurse performance is very important for the success of hospital services to provide patient satisfaction in obtaining maximum nursing care services. Nurse competency in the context of spiritual care is parallel to the nursing process, namely conducting assessments, formulating nursing diagnoses, preparing nursing plans and interventions, and evaluating the patient's spiritual needs. This research aimed to analyze the performance of nurses based on aspects of belief (Religious belief), ritualistic/worship (Religious practice), experience (Religious feeling), knowledge (Religious knowledge), and consequences/application (Religious effect) at Ibnu Sina Hospital Makassar. The research location will be carried out in the inpatient room at Ibnu Sina Hospital Makassar, the sample used is 110. The sampling technique used was proportional random sampling. Ibnu Sina Hospital is one of the hospitals whose service process is always based on Islamic values, so it is important to study the relationship between the concept of Islamic values and the aspect of religiosity. Ibnu Sina Hospital is a hospital whose service process is always based on Islamic values, so it is important to study the relationship between the concept of Islamic values in the aspect of religiosity and the performance achievements of nurses in serving their patients. Based on the research results, it is known that the religious effect dimension is the dimension that contributes most to the preparation of a religiosity-based nurse performance model.